2021
DOI: 10.1259/bjro.20210048
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of body composition and association with clinical outcomes in patients with lung and colorectal cancer

Abstract: Objectives: To assess body composition in patients with non-small cell lung cancer (NSCLC) and colorectal cancer using whole-body MRI and relate this to clinical outcomes. Methods: 53 patients with NSCLC (28 males, 25 females; mean age 66.9) and 74 patients with colorectal cancer (42 males, 32 females; mean age 62.9) underwent staging whole-body MRI scans, which were post-processed to derive fat mass (FM), fat free mass (FFM) and skeletal muscle (SM) indices and SM fat fraction (FF). These were compared betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In similar image-based studies, a higher SAT volume was associated with better progression free survival (PFS) and BFM ratio >22% was predictive of longer OS ( 55 , 58 ). Sakai et al reported increased length of hospital stay with increased skeletal muscle fat fraction and sarcopenia ( 59 ).…”
Section: Obesity and Survival Outcomes Of Lung Cancermentioning
confidence: 99%
“…In similar image-based studies, a higher SAT volume was associated with better progression free survival (PFS) and BFM ratio >22% was predictive of longer OS ( 55 , 58 ). Sakai et al reported increased length of hospital stay with increased skeletal muscle fat fraction and sarcopenia ( 59 ).…”
Section: Obesity and Survival Outcomes Of Lung Cancermentioning
confidence: 99%